Author Correction: Increased stiffness of the tumor microenvironment in colon cancer stimulates cancer associated fibroblast-mediated prometastatic activin A signaling - Jessica Bauer (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.